First-Principles Study on Evolution of Magnetic Domain in Two-Dimensional BaTiO3 Ultrathin Film Doped with Co under Electric Field - Gao, Haigen; Tang, Yu; Liao, Qilong; Zhao, Xiangyu; Wang, Bing (Nanomaterials (Basel, Switzerland), 2024)
The magnetization mechanism of Co-doped BaTiO3 ultrathin films is a subject of debate, which results in difficulties with the design of new multiferroics based on BaTiO3 matrixes. With the aid of a first-principles approach, it was observed that when the interstitial site and Ti vacancy were filled with Co, the configuration behaved in a nonmagnetic manner, indicating the significance of the Co content. Moreover, in the case of Co substituting two neighboring Ti atoms, when a direct current field was applied in the [100] direction, the magnetic domains excluding those in the [100], [010], and [001] directions were directed away. Further, the magnetoelectric constant was evaluated at ~449.3 mV/cmOe, showing strong magnetoelectric coupling at room temperature. Clearly, our study indicates that strict control of Ba, Ti, O, and Co stoichiometry can induce an electric and magnetic field conversion in two-dimensional BaTiO3 and may provide a new candidate for single-phase multiferroics for application in next-generation multifunctional devices.